Basidiomicetos de Costa Rica Exobasidiales, Cryptobasidiales. Notas históricas, taxonómicas y fitogeográficas - Gómez, Luis D; Kisimova-Horovitz, Liuba (Revista de Biología Tropical, 1997)
The Exobasidiá.les, Exobasidiaceae, are represented in Costa Rica by two genera: Exobasidium whicl1induces hypertrophies in leaves and flowers Of Ericaceae:Exobasidium vaccinii on species of V áccinium and P ernettya and E. gaylussaciae onMacleania and Sátyria; Exobasidiumflos·cavendishiae sp.nov., which causes hypertrophy on theflotá.l bractsof Cavendishia capitulara; Exobasidium ralamancense sp. nov. which causes leilfgá.lls in Vaccinium eonsanguineur/1. which resemble large, pendent "inilorescences" and E. rhododendri which infests cultivated ericads,e.g.;, Rhododendron. A new host record for neotropica1 Exobasidialesis herc.described asExobasidi¡’¡l’(leSealloniae, a shoot . parasite otEseallon.ia myrtillóidesin theSaxifragaceae. The species of KordyafU]., parasitíc onlllonocots, is represented by K. tradescantiae, on Crytobaelinaceae. The general distribution of Exobasidi